2023
DOI: 10.1002/adma.202209135
|View full text |Cite
|
Sign up to set email alerts
|

Encapsulating High‐Temperature Superconducting Twisted van der Waals Heterostructures Blocks Detrimental Effects of Disorder

Abstract: High‐temperature cuprate superconductors based van der Waals (vdW) heterostructures hold high technological promise. One of the obstacles hindering their progress is the detrimental effect of disorder on the properties of the vdW‐devices‐based Josephson junctions (JJs). Here, a new method of fabricating twisted vdW heterostructures made of Bi2Sr2CuCa2O8+δ, crucially improving the JJ characteristics and pushing them up to those of the intrinsic JJs in bulk samples, is reported. The method combines cryogenic sta… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
8
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
5
1

Relationship

2
4

Authors

Journals

citations
Cited by 24 publications
(10 citation statements)
references
References 35 publications
(55 reference statements)
0
8
0
Order By: Relevance
“…At the top and bottom surfaces of the BSCCO crystal, a subunit cell degraded region (dark area) can be observed due to a 30 min exposure of the flake to the glovebox atmosphere (Ar: 99.999%, O 2 ≤ 0.1 ppm, H 2 O ≤ 0.1 ppm) between the crystal exfoliation and the stacking of the membrane on top of it. In our system, we are able to preserve interface superconductivity and crystalline order in regions exposed less than 1 min to the Ar atmosphere at cryogenic temperatures. , A pristine BSCCO/Au interface can thus be created by a quick stacking of the circuit on top of the crystal, which is, however, beyond the scope of the present study.…”
Section: Methodsmentioning
confidence: 89%
See 1 more Smart Citation
“…At the top and bottom surfaces of the BSCCO crystal, a subunit cell degraded region (dark area) can be observed due to a 30 min exposure of the flake to the glovebox atmosphere (Ar: 99.999%, O 2 ≤ 0.1 ppm, H 2 O ≤ 0.1 ppm) between the crystal exfoliation and the stacking of the membrane on top of it. In our system, we are able to preserve interface superconductivity and crystalline order in regions exposed less than 1 min to the Ar atmosphere at cryogenic temperatures. , A pristine BSCCO/Au interface can thus be created by a quick stacking of the circuit on top of the crystal, which is, however, beyond the scope of the present study.…”
Section: Methodsmentioning
confidence: 89%
“…Additionally, twisted interfaces between cuprate crystals have been proposed as an adaptable platform for Josephson junctions with controllable coupling, which is a desirable feature for quantum applications. Thin BSCCO films promise to become an important platform for quantum sensors and detectors since bolometers fabricated from thin structured BSCCO crystals demonstrated a high level of single-photon sensitivity above 25 K. , Yet, the main challenge for building these structures is to maintain the superconducting phase of thin BSCCO crystals while integrating them into an electrical circuit, as the oxygen dopants are mobile at temperatures exceeding 200 K. , Furthermore, thin BSCCO flakes easily react with water leading to structural changes and modification of the oxygen doping level, which is crucial since altering the doping can drive the BSCCO film into an insulating phase. The preservation of interface superconductivity of the BSCCO crystal has been recently achieved by means of a cryogenic exfoliation technique combined with a solution-free stencil mask approach, enabling the fabrication of electrical devices entirely in an inert atmosphere. ,, The bottleneck hindering the realization of functional integrated circuits based on cuprate superconductors is the metallization of atomically thin crystals. The previously mentioned stencil mask approach enables the realization of simple electrical contacts in a single-layer geometry through the thermal evaporation of relatively low melting metals, such as gold, while providing a resolution down to 1 μm .…”
Section: Introductionmentioning
confidence: 99%
“…This is because the pressing of the elastomer stamp during the transfer process can lead to deformation of the supporting elastomer by a stress that is much higher than the strength of 2D materials, , and the incomplete release of 2D materials exists owing to the strong adhesion between supporting layer and 2D materials (Figure e,f). Although some works have applied temperature control to kinetically control the adhesion of elastomer stamps, the complete release of 2D materials on arbitrary substrate still remains a challenge.…”
Section: Conventional Transfer Methodsmentioning
confidence: 99%
“…1,9−11 To mitigate these issues, stencil mask lithography and limited-heating evaporation have been employed to reduce the damage of electrical contact fabrication in relatively thick flakes. 10,12,13 Additionally, a cold welding approach has been developed to preserve the ML sample quality, 1 although this method requires implementing a series of intricate processes in a stringent environment. In this study, we propose an alternative approach to investigate the superconductivity in atomically thin Bi2212 using ultrafast optical pump−probe spectroscopy, a noninvasive probe with micrometer-sized spatial resolution that allows us to study the interaction of 2D-HTSCs with different local environments.…”
mentioning
confidence: 99%
“…Recent experiments have revealed that novel phenomena such as the interfacial Josephson effect and superconducting diode effect can emerge in artificially twisted Bi2212 stacks. Theoretically, it has been predicted that such twisted stacks can host more exotic physics, including topological superconductivity with broken time-reversal symmetry. However, fabricating high-quality cuprate devices and probing their intrinsic properties through transport measurements remain challenging. One of the primary challenges lies in the susceptibility of atomically thin Bi2212 to degradation during conventional nanofabrication processes due to oxygen dopant loss and reaction with moisture. , To mitigate these issues, stencil mask lithography and limited-heating evaporation have been employed to reduce the damage of electrical contact fabrication in relatively thick flakes. ,, Additionally, a cold welding approach has been developed to preserve the ML sample quality, although this method requires implementing a series of intricate processes in a stringent environment. In this study, we propose an alternative approach to investigate the superconductivity in atomically thin Bi2212 using ultrafast optical pump–probe spectroscopy, a noninvasive probe with micrometer-sized spatial resolution that allows us to study the interaction of 2D-HTSCs with different local environments.…”
mentioning
confidence: 99%